2021
DOI: 10.1021/acs.energyfuels.1c01328
|View full text |Cite
|
Sign up to set email alerts
|

Probing Nanomechanical Properties of a Shale with Nanoindentation: Heterogeneity and the Effect of Water–Shale Interactions

Abstract: The mechanical properties of shale are critical for the extraction of gas and oil from nanoporous shale. In this study, nanoindentation tests with the accelerated property mapping mode were used to obtain the localized quantitative mechanical properties (the elastic modulus and hardness) of the tested shale sample. X-ray diffraction was used to analyze the bulk mineral composition. The Gaussian mixture model and k-means algorithm were used to fit the data and identify distinct mineral phases based on load–disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…They found that radial cracks were observed on the boundaries of brittle minerals and relatively weak minerals, while shear cracks were detected on the layered silicates and organic matter. Although the elastic and plastic behaviors of minerals in shale samples were similar, the magnitudes of plastic work to total work varied with formations and depths (Cheng et al., 2022; Liu et al., 2021, 2022; Yang et al., 2020). Besides, the mineral composition can affect the frictional properties of rocks.…”
Section: Introductionmentioning
confidence: 99%
“…They found that radial cracks were observed on the boundaries of brittle minerals and relatively weak minerals, while shear cracks were detected on the layered silicates and organic matter. Although the elastic and plastic behaviors of minerals in shale samples were similar, the magnitudes of plastic work to total work varied with formations and depths (Cheng et al., 2022; Liu et al., 2021, 2022; Yang et al., 2020). Besides, the mineral composition can affect the frictional properties of rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Shale gas reservoirs have strong anisotropy and heterogeneity [11][12][13] . A majority of pores in rocks are micropores with a diameter between 2 and 50 nanometers, mesopores with a diameter between 2 and 50 nanometers, and macropores with a diameter exceeding 50 nanometers [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%